2012
DOI: 10.1371/journal.pone.0039215
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mycobacterium indicus pranii Immunotherapy as an Adjunct to Chemotherapy for Tuberculosis and Underlying Immune Responses in the Lung

Abstract: BackgroundThe 9-month-long chemotherapy of tuberculosis often results in poor compliance and emergence of drug-resistant strains. So, improved therapeutic strategy is urgently needed. Immunotherapy could be beneficial for the effective management of the disease. Previously we showed the protective efficacy of Mycobacterium indicus pranii (MIP) when given as prophylactic vaccine in animal models of tuberculosis.MethodsWe sought to investigate whether MIP can be used as an adjunct to the chemotherapy in guinea p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 49 publications
0
38
0
2
Order By: Relevance
“…[15][16][17] M. indicus pranii is a nonpathogenic, saprophytic, rapidly growing atypical mycobacterium species that has shown clinical benefit when administered as a heat-killed intradermal formulation in patients with leprosy and that may have benefits in patients with pulmonary tuberculosis and HIV infection. 16,[18][19][20][21][22] We hypothesized that intradermal M. indicus pranii could be effective in suppressing inflammation and its sequelae in patients with tuberculous pericarditis.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] M. indicus pranii is a nonpathogenic, saprophytic, rapidly growing atypical mycobacterium species that has shown clinical benefit when administered as a heat-killed intradermal formulation in patients with leprosy and that may have benefits in patients with pulmonary tuberculosis and HIV infection. 16,[18][19][20][21][22] We hypothesized that intradermal M. indicus pranii could be effective in suppressing inflammation and its sequelae in patients with tuberculous pericarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated doses of intradermal heat-killed M. indicus pranii immunotherapy may reduce inflammation associated with TB and increase the CD4 + T-cell count in persons infected with HIV. [52][53][54] Adjunctive therapy with prednisolone for 6 weeks and treatment by M. indicus pranii for 3 months did not have a significant effect on the combined outcome of death from all causes, cardiac tamponade requiring pericardiocentesis, or constrictive pericarditis. [55] Both therapies were also associated with an increased risk of HIV-associated cancer.…”
Section: Immunotherapymentioning
confidence: 94%
“…Macrophages differentiated from monocytes were transferred into 24 well tissue culture plates (Corning, Tewksbury MA, USA) (1 × 105 cells per well). Freshly prepared Mm, BCG, and H37Ra were subsequently added to each well with a multiplicity of infection (MOI) of 0.5 based on trial results with different MOIs.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, studies have shown that the prophylactic and therapeutic vaccines, including heat-killed and live attenuated mycobacteria, and DNA/proteins of mycobacterial origin, appear to be more safe and effective 24. These vaccines have been used both as adjuvants for immunization and immunotherapies for several diseases such as Mtb infection and bladder cancer;59 however, all of these vaccines were known to control, but not to eradicate, Mtb infection 10,11. Theoretically speaking, mycobacterial priming vaccines of an improved whole organism could potentially induce a more effcient immune response than other vaccines such as those from bacterial components 12.…”
Section: Introductionmentioning
confidence: 99%